Pengaruh Penambahan Serbuk Karet dan Serbuk Cangkang Telur Terhadap Parameter Tanah Lempung pada Pengujian Konsolidasi dan Kuat Geser Langsung - Nurfatihah Nurfatihah; Sri Wulandari (Jurnal Teknik Sipil, 2023)
Soil improvement methods can use waste materials to improve the geotechnical properties of the soil. Disposal of waste tires and waste eggshells can cause several problems for the environment. Therefore, one way to deal with it is to recycle used tires as materials for soil improvement. This study aims to determine the effect of the most optimum value on the addition of rubber powder (SK) from waste tires and eggshell powder (SCT) on clay soil parameters. The research was carried out through laboratory tests by testing index properties and engineering properties. Based on the USCS soil classification, the soil sample taken from Hambalang, Citeureup, Bogor, was the organic clay. The percentage of addition of SCT is the same for each variation of mixed soil, namely 3% with the addition of SK which is 9%, 12%, and 17%. The results show that the addition of SK and SCT can increase the internal shear angle from 24,17o in the original soil to 27,82o at 3% SCT+12% SK, increasing the cohesion value from 5,88 kN/m2 to 7,29 kN/m2. The results of the consolidation test showed that at levels of 3% SCT+12% SK, the compression index decreased from 0,19 to 0,12, and the void ratio from 0,85 to 0,55. The results showed that the addition of rubber powder and eggshell powder could improve shrinkage and increase the density of organic clay.